Acoustics on display: collecting and curating sound at the Science Museum - Dr Jennifer Rich (Science Museum Group Journal, 2017)
This article traces sound as it echoes through approaches to displaying the Science Museum’s acoustics collection over the course of the twentieth century. Focusing on three key moments in the collection’s historical development, the article explores the role of sound as both medium and object of museum display. Each moment exposes how the practice of using sound to interpret sounding objects was articulated and problematised by past generations of museum practitioners. Each moment, too, exposes the problem of sound as a potential threat to the cultural politics of a national museum, disrupting the economies of the senses governing the museum as a consecrated space for learning. Thinking historically, this article excavates a body of practical experience and expertise which has the potential to support a growing body of modern museum practitioners using sound as a medium for, and object of, museum display.